2004
DOI: 10.1111/j.1468-1293.2004.00206.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolated antibodies against the core antigen of hepatitis B virus in HIV‐infected patients

Abstract: SummaryThe aim of this study was to describe the frequency and significance of isolated antibodies against the hepatitis B virus (HBV) core antigen (HBc) in 2185 HIV-infected patients of the Aquitaine Cohort. Antibodies against HBc were found in 372 subjects (17%). Patients with isolated anti-HBc antibodies were more frequently coinfected with hepatitis C virus (HCV) (58.2%) than those who were anti-HB surface (HBs) antibody positive (22.9%, Po0.001) and those who were dually reactive anti-HBs/antiHBc antibody… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
27
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 9 publications
(17 reference statements)
6
27
1
1
Order By: Relevance
“…This event has been previously reported in only one study [17] , in which a higher frequency of "anti-HBc alone" status was also found among women. Nevertheless, in our study the proportion of women in the "anti-HBc alone" group was the same as that in the past hepatitis group (30.9%).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…This event has been previously reported in only one study [17] , in which a higher frequency of "anti-HBc alone" status was also found among women. Nevertheless, in our study the proportion of women in the "anti-HBc alone" group was the same as that in the past hepatitis group (30.9%).…”
Section: Discussionsupporting
confidence: 71%
“…Occult hepatitis prevalence data reported in "antiHBs alone" HIV-positive patients varies greatly from 0% to 89.5% [1][2][3]9,12,17,20,21] . However, in those studies that have found viral replication, detected viral load was usually very low (< 10 3 copies/mL) [3,20] .…”
Section: Discussionmentioning
confidence: 99%
“…Both patients had detectable HIV-1 RNA levels, although only at 235 and 285 copies/mL; 1 had a CD4-lymphocyte percentage below threshold for age (21%); and both were receiving 3TC-containing HAART for just over 1 year. The presence of isolated HBcAb is common among HIV-infected individuals and has been associated with the presence of concurrent HCV infection [32][33][34]. Whether the results for these 2 patients reflect immunity with undetectable HBsAb, occult HBV infection, or a false-positive HBcAb result is unclear.…”
Section: Resultsmentioning
confidence: 99%
“…Standard 3-dose HBV vaccine regimens confer protection in >95% of immunocompetent children [35], but HIVinfected children have lower seroconversion rates. Even when seroconversion does occur, attrition of antibody with time, even among the immunocompetent, is also possible [30][31][32][33]. Tanzania's national immunization program does not include a birth dose of hepatitis B vaccine, but rather a 3-dose regimen beginning at 4 weeks of life in conjunction with other routine vaccinations.…”
Section: Resultsmentioning
confidence: 99%
“…However, the results are not conclusive since liver biopsy for HBV DNA intrahepatic detection was not performed, and children participating in the study showed a high median age and good clinical and immunological status, as good as those in similar studies. Thus, the interpretation of the HBV marker profile in the 6 patients with probable OBI in the present study remains controversial in terms of its being a surrogate marker for HBV/HIV coinfection, or possibly not in the event of additional immunosuppresion (144,152,157,160). …”
mentioning
confidence: 81%